2013
DOI: 10.1016/j.jmarsys.2012.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Trace metals in the NE Atlantic coastal zone of Finisterre (Iberian Peninsula): Terrestrial and marine sources and rates of sedimentation

Abstract: Abstract. The biogeochemical patterns of bioactive metals (Cd, Co, Cu, Ni, V and Zn) and Pb were studied in the Corcubión Sound, an area close to Cape Finisterre (NW Iberian Peninsula). Seasonal patterns of dissolved and particulate trace metals in the freshwater and seawater, as well as in the phytoplankton were determined during three upwelling events in the winter, late spring and summer of 2005. Metals were also analysed in the surface and to 1 m-depth in the sediments. Upwelling patterns permit the discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 80 publications
0
8
2
Order By: Relevance
“…Our surface water DPb concentration of 40.2 ± 7.5 pmol kg À1 (n = 109) along the shelf break in 2014-2015 showed at least a fourfold decrease compared to previous reports for the region (Figure 2e and Table S2) (Brügmann et al, 1985;Cotté-Krief et al, 2002;Helmers & Van der Loeff, 1993;Lambert et al, 1991;Muller et al, 1994) and were generally lower in comparison to other European shelf waters over the last 4 decades (Kremling & Streu, 2001;Laumond et al, 1984;Monteiro et al, 2015;Pohl et al, 2011;Prego et al, 2013;Waeles et al, 2008). The diminishing DPb concentrations over the last two decades form a success of the phaseout process of leaded gasoline.…”
Section: Resultscontrasting
confidence: 58%
“…Our surface water DPb concentration of 40.2 ± 7.5 pmol kg À1 (n = 109) along the shelf break in 2014-2015 showed at least a fourfold decrease compared to previous reports for the region (Figure 2e and Table S2) (Brügmann et al, 1985;Cotté-Krief et al, 2002;Helmers & Van der Loeff, 1993;Lambert et al, 1991;Muller et al, 1994) and were generally lower in comparison to other European shelf waters over the last 4 decades (Kremling & Streu, 2001;Laumond et al, 1984;Monteiro et al, 2015;Pohl et al, 2011;Prego et al, 2013;Waeles et al, 2008). The diminishing DPb concentrations over the last two decades form a success of the phaseout process of leaded gasoline.…”
Section: Resultscontrasting
confidence: 58%
“…The number of studies reported in the literature regarding metals concentrations in the Iberian Peninsula coast are limited (e.g. van Geen et al, 1991;Leal et al, 1997;Cotté-Krief et al, 2000;Caetano and Vale, 2003;Cánovas et al, 2007;Santos-Echeandía et al, 2012;Prego et al, 2013; Table 2, this paper). Most of these studies were not particularly devoted to the effect of upwelling upon the distribution of the metals.…”
Section: Labile Fraction Of Dissolved Metals Fate During Upwellingmentioning
confidence: 92%
“…Particularly in some species of diatoms it is involved in the carbonic anhydrase (CA) activity (Morel and Price, 2003) and in one coccolithophore species, it regulates the alkaline phosphatase activity (Shaked et al, 2006). Despite the controversial ϲ opinions about Cd behaviour (Morel et al, 1991;European Commission, 2002;Prego et al, 2013), some authors agree about Cd biological functions, which include competition with Zn bioavailability in CA activity under Zn-limited conditions (Morel et al, 1991;Morel and Price, 2003). Both metals have a nutrient-type distribution in the ocean (Bruland and Lohan, 2003;Wyatt et al, 2014), often strongly correlated with the phosphate, nitrate and silicic acid (Bruland and Lohan, 2003;Croot et al, 2011;Wyatt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contents were lower than in highly polluted places such as the Mar Chiquita Lagoon, Argentina (BELTRAME et al, 2009) and the Dakar Coast (DIOP et al 2014); moderately polluted estuaries like the Scheldt Estuary (ZWOLSMAN; VAN ECK, 1999) and the Changjiang Estuary, China (HSU; LIN, 1998), and comparable to well preserved systems such as Jaguaripe Estuary, Bay of Santos, Brazil (HATJE et al, 2012) and Corcunbion Sound, Iberian Peninsula (PREGO et al, 2013).…”
Section: Particulate Metalsmentioning
confidence: 89%